SYSTEM INTEGRATION OF MEMBRANE CONTACTOR AND PHOTOCATALYTIC REACTOR FOR CO2 CONVERSION INTO FORMIC ACID - Rina Ayu Astuti, Andi
More than 75% of greenhouse gases (GHGs) in the atmosphere is CO?, and power plants contribute nearly two-thirds to total CO? emissions. Therefore, if the concentration of CO2 from exhaust emissions can be significantly reduced, the impact of global warming will also decrease. Carbon Capture and Utilization (CCU) schemes have become increasingly popular because they not only reduce CO? emissions but also convert them into valuable products. One promising product is formic acid (HCOOH) due to its use as raw material for various industrial chemical products. In this research, CO2 capture using a membrane contactor and its conversion into formic acid through a photocatalytic reactor form a sequentially operating integrated system. Gas-liquid absorption on membrane contactors produces dissolved CO?, which is then converted into formic acid using a photocatalyst activated by photon energy (UV/visible light). One innovation in this research is the use of trietanolamin (TEA), which serves a dual function: as a CO2 absorbent in the membrane contactor and as an electron donor in the photocatalysis reactor. In this process, protons (H+) from water oxidation and electrons (e-) from the electron donor are required for the complete photoreduction of CO2 to HCOOH. TiO2 and ZnO were used as base catalysts due to their abundance in nature and their band gap energies, which are equal to or greater than the reduction potential of CO2 to formic acid (-0.61 eV). Through the development of photocatalysts based on heterojunction principles, this research is expected to be applicable to gas mixtures resembling power plant emissions with low CO2 concentrations (15 %- mol), utilizing energy from the visible light spectrum (sunlight or LEDs). To date, no similar studies or reviews have combined membrane contactors and photocatalysis for CCU, including a discussion of the adsorption mechanism of CO2 photoreduction into formic acid. The stages of this research began with CO2 capture using a membrane contactor, followed by CO2 photoreduction into formic acid, and the development of selective photocatalysts to produce formic acid. The parameters in each stage of the research are interconnected, so the sequence of the study has been designed to achieve the objectives of the subsequent stages. The CO2 capture stage aims to determine the CO2 gas concentration, operating time, type of absorbent, maximum absorption capacity, and reactive CO2 absorption rate. The results show that absorption using TEA solution has a higher flux, 57.863 x 10-5 mol/m2.s, compared to NaOH solution with a flux of 57.09 x 10- 5 mol/m2.s. The maximum absorption capacity using TEA solution was also higher, at 0.957 mol CO2/mol solvent, compared to NaOH at 0.75 mol CO2/mol solvent at a gas flow rate of 800 mL/min, leading to its selection as the reaction medium for the next stage of the research. The maximum absorption time achieved in 1.5 hours. The initial stage of CO2 photoreduction aims to determine the reaction medium, the basic catalyst, the adsorption mechanism, and the influence of CO2 photoreduction parameters. According to the research results, both processes can occur if the reaction medium is TEA, with ZnO semiconductor producing a higher concentration of formic acid than TiO2, at 345.44 ?mol/L.gcat over 4 hours. Therefore, ZnO was selected for the next stage of the research. The adsorption mechanism of 2H+ and HCOOH, which is stronger compared to CO2, best fits the experimental and Density Functional Theory (DFT) computational data. The formic acid concentration can be predicted through the integration model of CO2 capture and photoreduction, where CHCOOH (photoreduction) = (400 U + 540,000) exp (0.042 t) – (-0.055 t + 67.33)0.5 at feed gas flow rate U over time t. Based on the CCD method and ANOVA, UV lamp power and pH solution were found to be significant parameters affecting photoreduction. The next phase of the research involves the development of ZnO-ZnS photocatalysts through variations in concentration and calcination temperature. The results show that the synthesis of ZnO and ZnS catalysts meets diffraction standards, with the highest wavelength reaching 405,18 nm (visible light spectrum). CO2 photoreduction activity into HCOOH showed the three best catalysts to be Z1, Z4, and Z2, with ZnO:ZnS molar ratios and calcination temperatures of (Z1) 1:2, 400°C, (Z4) 1:2, 500°C, and (Z2) 1:1, 400°C, yielding HCOOH production rates of 0.643; 0.554; and 0.626 mmol/L.gcat.h, respectively. Using a 15% CO2 feed and LED light produced the highest formic acid levels, at 0.936 mmol/L.gcat and 0.394 mmol/L.gcat over 4 hours of operation. The use of visible light and Z1 demonstrated higher selectivity for formic acid production. EIS analysis indicates that Z1 exhibits lower electrochemical resistance. SEM analysis reveals the presence of nanorods (ZnO) and globular structures (ZnS) with sizes ranging from 50–100 nm, while HRTEM analysis confirms the ZnO-ZnS diffraction patterns. After 4 hours of photoreduction, most of the ZnO-ZnS catalyst peaks remained stable. The calculations show that the yield and productivity of CO2 to HCOOH increased up to 8.41-fold after catalyst modification, at 2.574 mmol/gcat and 0.644 mmol/h respectively. This CO2 utilization is expected to meet the growing demand for formic acid, the CO2-derived product with the highest market value, while supporting the implementation of circular economy.